Effective Communication as a Pillar of Public Policy Implementation at DUKCAPIL Prima in South Sulawesi - Kondolele, Sukarniaty; Sultan, Moehammad Iqbal; Akbar, Muh. (Universitas Mercu Buana, 2025)
This research aims to analyse the application of the communication model in the implementation of the DUKCAPIL Prima policy in South Sulawesi Province, and evaluate the factors that influence the effectiveness of communication in public policy. The approach used in this research is qualitative with a case study design. Data collection was conducted through in-depth interviews with the Head of the DUKCAPIL Office of South Sulawesi Province and participatory observation related to policy communication activities. The results showed that the communication model applied consisted of one-way communication and gradual communication, which proved effective in conveying policies from the central government to the district/city level. In addition, the use of various forms of messages such as instructional, motivational, informational, and feedback as well as the utilisation of various communication media (print media, radio, television, and social media) increase the effectiveness of policy delivery to the community. The significance of this research lies in a deeper understanding of the importance of a systematic and integrative communication model in the implementation of public policies, especially in the field of population administration and civil registration.